Analysis of the Role of Education and Its Influence on Socio Cultural Change - Khairunnisa; Anis Fauzi; Ahmad Qurtubi (Journal of Educational Analytics, 2023)
This article uses a literature study approach and is included in qualitative research. Several stages of data presentation are applied in this paper, namely data restatement, description to map data patterns, and interpretation to highlight the exact meaning of the role of education and its influence on socio-cultural change. Every human being during life can be sure to experience a lot of changes. Change can be both good and bad, and one of the factors is education. In a social and cultural perspective, education has a prominent role so that it is able to develop individual capacities to become good citizens and, in building society, carry out cultural and social transformation, including norms, habits, and attitudes.